Mild Renal Injury in Behcet's Disease - Sahin, I; Noyan, T; Karaman, E; Yalcinkaya, AS; Metin, A; Akpolat, T (Taylor & Francis Ltd, 2004)
Aim: The aim of this study is to investigate the frequency of microalbuminuria and abnormal urinary beta(2)-microglobulin excretion in patients with Behcet's disease (BD). Materials and Methods: Twenty-eight patients and 27 healthy controls were included in this study. Urine albumin/creatinine and beta(2)-microglobulin/creatinine ratios were calculated. Results: The frequency of microalbuminuria and abnormal urinary beta(2)-microglobulin excretion was higher among patients with BD than in control group, but this was not statistically significant (p>0.05). Conclusion: Microalbuminuria and abnormal beta(2)-microglobulin excretion are markers of renal injury, which have not been investigated in BD previously. Renal injury in BD is more frequent than has been recognized and it is most often in mild nature.
Keywords: Behcet's Disease; Renal Injury; Microalbuminuria; B-2-Microglobulin